Survey of parasitic fauna data from wild animals through coproparasitological diagnosis in Southern Brazil - Julia Somavilla Lignon; Diego Moscarelli Pinto; Tamires Silva dos Santos; Giulia Ribeiro Meireles; Camila Gonçalves da Silveira; Bianca Conrad Bohm; Felipe Geraldo Pappen; Silvia Gonzalez Monteiro; Mauro Pereira Soares; Raqueli Teresinha França; Fábio Raphael Pascoti Bruhn (BMC Veterinary Research)
Abstract Background The proximity between people and their domestic animals with wild animal populations can result in the spread of diseases with a significant impact on public health. Infection by parasites in wildlife is considered an important bioindicator of the current state of ecosystems, and studying the epidemiology of these infections is essential for a better understanding of natural foci. However, research on parasites in southern Brazil, especially in Rio Grande do Sul (RS), is considered incipient. Therefore, in this study, we aimed to identify the parasitic fauna of wild animals in the southern region of RS through fecal parasitological diagnosis. We processed 82 fecal samples from wild animals - including birds, mammals, and reptiles - from cities within the microregion of Pelotas, using the Zinc Sulfate Centrifugal Flotation, Spontaneous Sedimentation and Oocyst Sporulation techniques. Results In 69.5% of the samples (93.1% of mammals, 47% of birds and 50% of reptiles), we found helminth eggs and/or protozoan cysts/oocysts, with strongylid-type eggs being the most frequent parasites (44.11%). Additionally, 64.9% of the positive samples were parasitized by at least one morphogroup with zoonotic agents (Taeniidae, Capillaria, Strongyloides, Spirometra, Lagochilascaris, Sarcocystis, Trichuris, Giardia, Ancilostomid, Physaloptera, Toxocara, Fasciola). We also recorded the first finding of Monocystis spp. in a Southern tamandua (Tamandua tetradactyla). Conclusions Thus, it was observed that the majority of the animals were parasitized and, consequently, susceptible to a wide range of pathogens of medical and veterinary interest, highlighting the importance of these hosts in the spread of parasites, especially those with zoonotic potential. However, the ecology of transmission and the role of these hosts in the life cycles of parasites should be further explored in other studies.